The Influence Of Ph And Concentration Of Phosphonate Inhibitor - Tests On Change Of Barium Sulfate Scale Morphology By Using Scanning Electron Microscope - Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2004)
Water injection is often used to keep maintaining reservoir pressure. Injected water (high in sulphate) mixes with formation water (high in barium) leading to the deposition of barium sulfate scale in the near wellbore, reservoir, production tubulars and topside equipment. Barium sulfate scale is unique scale deposit and the least soluble of the scales. The deposition of oil field scale is a potentially damaging problem which reduces fluid flow resulting in a decline in oil production. The best approach to solving the problems of scale formation is to prevent or inhibit deposition and this is more effective than scale removal. The use of scale inhibitor can be effective method for preventing scalealthough their effectiveness is controlled by experimental conditions. Therefore, it is very important to know factors that influence barium sulfate scale. The maintopic of this paper is â€œThe Influence of pH and Concentration of Inhibitor Solution - Tests on Change of Barium Sulfate Scale Morphology by Using Scanning Electron Microscopeâ€. Hopefully, the results of laboratory test presented this paper give useful and valuable information not only for LEMIGAS, but also for oil industry, chemical manufacturers and universities, then other institutions.